Efficacy of different pharmaceutical forms of Curcuma longa or curcumin in reducing oral mucositis severity and incidence in cancer patients: a systematic review and meta-analysis - Amatto, Pedro de Padua G.; Chaves, Lucas; França, Suzelei de Castro; Carvalho, José Carlos Tavares; Carmona, Fabio; Pereira, Ana Maria Soares (Frontiers in Pharmacology, 2025)
BackgroundCurcuma longa L. (turmeric, Zingiberaceae) has been traditionally used for its anti-inflammatory, wound-healing, and antimicrobial properties. These characteristics have made it a key component in managing inflammatory and ulcerative conditions like oral mucositis (OM). This study aimed to evaluate the effectiveness of various pharmaceutical formulations of C. longa or curcumin in reducing the OM severity, incidence and associated pain in patients undergoing chemotherapy and/or radiotherapy for cancer.MethodsThis systematic review and meta-analysis of randomized clinical trials was conducted according to PRISMA guidelines, registered in PROSPERO (#CRD42024504111). Searches were performed in PubMed, Embase, and Cochrane databases. Studies comparing C. longa or curcumin with placebo in cancer patients experiencing oral mucositis, reporting outcomes such as the World Health Organization Oral Mucositis Grading Scale, pain scores (visual analogue scale), or OM incidence were included. Risk ratios and weighted mean differences with 95% confidence intervals were calculated using fixed- or random-effects models.ResultsSix studies with 159 patients (mean age ∼50 years, 40% women) were included. C. longa extracts, curcumin, or nanocurcumin were administered in capsules, mouthwash, or gel formulations. The pooled analysis showed significant reductions in WHO scores and oral pain compared to placebo. OM incidence decreased by 6% overall, with a notable 37%-reduction observed in patients using curcumin-containing mouthwash during radiotherapy alone. Subgroup analyses revealed consistent benefits across all oncological treatments.ConclusionC. longa, curcumin, or nanocurcumin in various formulations, effectively reduce OM severity and pain while curcumin-containing mouthwash reduced OM incidence in cancer patients undergoing treatment.Systematic Review Registrationidentifier CRD 42024504111.